Timeless evolution of walking and pace strategy of women`s race walking - Fitili, P.; Giovanis, V. (Pedagogy of Physical Culture and Sports, 2020)
Background and Study Aim. The purpose of this research was to study the timeline evolution of walking, as well as the Pacing Strategy Profiles of high-level women in the 20 km of race walking. Material: The practical example of applying the theoretical basis was made during the Women`s Greek Championship (Megara 2016), in which 12 athletes aged 19 to 40 participated (28.50 ± 7.20). Material and Methods. The certified distance of the 20km route was divided into 10 sections of 2 km each. The same happened with the times (intermediate, final) corresponding to the individual sections (2 km) of the route. The athletes were divided into 4 groups: the first 3, those who finished 15% slower than the first, those who finished 15% - 30% slower, and those who finished more than 30% slower than the winner. Finally became comparison of the first 6 and last 6 athletes` groups. Results. The individual pace strategies that describe the tactics of the athletes in this race have been calculated. It was found that the winners of the race used Even Pacing Strategy, maintaining a steady speed on most of the route. As the level of women athletes became lower, Variable Pacing Strategy was used, while the athletes who finished last did not seem to be able to maintain any particular pacing strategy. Conclusions. It is suggested that athletes should follow Even Pacing Strategy during the race in order to improve their performance.